Hospital readmissions among older people with intellectual disability in comparison with the general population - Axmon, A. (J Intellect Disabil Res, 2019)
BACKGROUND: Older people with intellectual disability have high multimorbidity and poor physical and mental health compared with the general population. Consequently, they have a greater need for health care. Hospital readmissions may be an indicator of the quality of health care. However, so far, only a few studies have investigated this outcome in populations of people with intellectual disability. None has focused on older people. METHOD: We identified a cohort of people with intellectual disability aged 55+ years and alive at the end of 2012 (n = 7936). Moreover, we established a reference cohort from the general population, one‐to‐one matched by sex and year of birth. Data on hospital visits during the period 2002–2012 were collected from the Swedish National Patient Register. Readmissions were defined as unplanned visits with the same diagnosis occurring within 30 days of discharge and with no planned visit for the same diagnosis during this time. RESULTS: Compared with the general population, people with intellectual disability had increased risk of readmissions for diseases of the nervous system [relative risk (RR) 2.62], respiratory system (RR 1.48), digestive system (RR 1.40) and musculoskeletal system and connective tissue (RR 2.10). Within these diagnostic groups, increased risks were found for arthropathies (RR 3.73), disorders of gallbladder, biliary tract and pancreas (RR 1.78), other diseases of intestines (RR 1.30), and other forms of heart disease (RR 1.23). Decreased risk of readmissions was found for mental and behavioural disorders (RR 0.78) and diseases of the circulatory system (RR 0.64). CONCLUSIONS: The increased risk for readmissions related to diseases of the nervous and musculoskeletal systems has a clear relation to the prevalence of comorbidities in these areas. People with intellectual disability often also have inborn limitations and damages in these systems which with time lead to complications and risk for diseases, which can be difficult to discover. The increased risk for readmissions for disease of the respiratory system, together with the already known increased prevalence of such diagnoses and their occurrence as a cause for death, warrants further investigations and considerations of potential preventive measures. The pattern of readmissions among older people with intellectual disability cannot be explained solely by a higher prevalence of disorders in this group. Our finding of increased risks for readmissions for diseases in the digestive system could be interpreted as communication problems, which sometimes result in too rapid discharges and their consequential early readmissions.